If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 5 = 10(x + 9) Reorder the terms: 5 + y = 10(x + 9) Reorder the terms: 5 + y = 10(9 + x) 5 + y = (9 * 10 + x * 10) 5 + y = (90 + 10x) Solving 5 + y = 90 + 10x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + y = 90 + -5 + 10x Combine like terms: 5 + -5 = 0 0 + y = 90 + -5 + 10x y = 90 + -5 + 10x Combine like terms: 90 + -5 = 85 y = 85 + 10x Simplifying y = 85 + 10x
| 4x+8=-7x+10 | | 5r^3✖️2r^1/2 | | 3t-6=-9 | | -.83y+0.17=.72y | | 4p-12=20p-24 | | 30n-38=5(1+6n) | | 2d+4=10+2.4d | | y+2=.25(x+4) | | 5(x)=20(1.93)x | | -7b-5=-7b-8 | | 2+3-90=r | | 1/3x-2=x-4 | | 5(x)=20(1.93)xX | | 17x=1500+-12y | | -19=5r-4 | | 14y+8=-34 | | y-10=.25(x-4) | | 6/11(x-5)=6 | | (2x-15)+(x+35)=180 | | 8d+15=-33 | | y-7=0.25(x+4) | | W/26-369=-354 | | 3x-4y=400 | | 14X^5-12X^4-48=0 | | 1.5=.5/x | | 7+25n^2=71 | | -5-8x=1-3x-4+13 | | 7(s-82)=28 | | y-9=0.16666(x+6) | | 6t+90=90t+90t+90t | | 5(z+8)=95 | | 2=a/55 |